Reporting of adverse events in muscle strengthening interventions in youth: A systematic review - Mack, D. E.; Anzovino, D.; Sanderson, M.; Dotan, R.; Falk, B. (Pediatric Exercise Science, 2023)
Clear definition, identification, and reporting of adverse event (AE) monitoring during training interventions are essential for decision making regarding the safety of training and testing in youths. Purpose: To document the extent to which AEs, resulting from intervention studies targeting muscle strengthening training (MST) in youth, are reported by researchers. Methods: Electronic databases (CINAHL, PubMed, SPORTDiscus, and Web of Science) were searched for English peer-reviewed articles published before April 2018. Inclusion criteria were: (1) average age <16 years, (2) use of MST, (3) statement(s) linked to the presence/absence of AEs, and (4) randomized controlled trials or quasi-experimental designs. Risk of reporting bias for AEs followed recommendations by the Cochrane Collaboration group. Results: One hundred and ninety-one full-text articles were screened. One hundred and thirty met all MST criteria, out of which only 44 (33.8%; n = 1278, age = 12.1 [1.1] y) included a statement as to the presence/absence of adverse events. The 86 other studies (66.2%) included no such statement. Of the reporting 44 studies, 18 (40.1%) indicated one or more adverse events. Of the 93 reported adverse events, 55 (59.1%) were linked to training or testing. Conclusions: Most MST studies in youth do not report presence/absence of adverse events, and when reported, adverse events are not well defined.